Demographic profile and epidemiology of injury in Mthatha, South Africa - Dhaffala, A (Makerere Medical School, 2013)
OBJECTIVE: To determine the magnitude, socio-demographic and epidemiological characteristics of injury at a Provincial referral hospital. METHODS: This review was conducted on all trauma patients admitted at the Mthatha Hospital Complex and Nelson Mandela Academic Hospital from the 1(st) January 1997 to the 31(st) December 2000. RESULTS: The incident rate of injuries was 3.2% (n=2460/75,833 total admissions). Injured patients were mostly black (80%) and males (ratio: 5 men: 1 woman). Only 8.1% of injured patients were transported to hospital by ambulances. The leading causes of injuries were inter-personal violence accounting for 60% of cases, and motor vehicle accidents accounting for 19%; of them 38% were due to poor visibility, over speeding, and fatigue. The overall mortality was 33% (n=821) independently predicted by poverty (OR=8.2 95%CI 6–11.1; P<0.0001) and age>40 years(OR=7.8 95%CI 7.7–12.1;P<0.0001). CONCLUSION: The burden of injury is a mass issue that warrants regional attention with quality of care and training.